Challenges for Legionella pneumophila detection in Indonesia - Rivia Gina Rahmawaty; Mochamad Helmi Aziz; Chairinda Dachwan; Erie Yuwita Sari; Ibnu Agus Ariyanto; Mardiastuti Wahid (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2022)
Legionella pneumophila (L. pneumophila) is widely known to cause respiratory illness outbreaks and remains underdiagnosed, including in Indonesia. Several diagnostic methods are available, yet none have been implemented as a routine diagnostic panel in most clinical microbiology laboratories in Indonesia. The urine antigen test is the cheapest and easy to perform. However, it only detects serogroup 1 of L. pneumophila, creating a blind spot for non-serogroup 1. Culture is the gold standard, but its sensitivity and turnaround time makes culture less feasible in a clinical setting. The direct fluorescent antibody is rapid, nonetheless, expertise and experience are needed to increase the sensitivity. Molecular methods, while very sensitive, cannot rule out contamination since the bacteria are mostly found in water. In order to validate which best method to be performed in Indonesia, a nationwide surveillance and validation study should be performed.